Neotype designation and redescription of Mesacanthion armatum Timm, 1961 (Nematoda, Enoplida) along with an updated taxonomic key to the species of Mesacanthion (Filipjev, 1927) De Coninck & Schuurmans Stekhoven, 1933 - Datta, Tridip Kumar (Zootaxa, 2026)
Neotype of Mesacanthion armatum is designated and the redescription is elaborated with novel morphological feature, along with comparative study of types descriptions, with the help of new specimens collected in the northeast coast of India. Despite of the dissimilarities between the original description and the present study, morphometrics along with morphological accounts were analysed. Relevance of those characters was then evaluated for confirmation to consider them as the same species. Furthermore, an updated species key of Mesacanthion is presented, along with discussion of morphological traits.